The impact of Transcranial Magnetic Stimulation on depressive symptomatology in patients with chronic pain disorders: A Systematic Review - Maria Inês Cunha Salgado (2024)
Objective: Transcranial Magnetic Stimulation (TMS) is a recognized therapy for treatment-resistant depression and has been studied for its potential in managing chronic pain. Knowing the intrinsic relationship between pain and depressive symptomatology, this systematic review aims to assess the impact of TMS applied on depressive symptoms in patients with chronic pain. Methods: Electronic databases were systematically searched until November 2023 for studies applying TMS in chronic pain patients, with assessment of both pain and depressive symptomatology. Results: From the records screened, 29 studies met the inclusion criteria for qualitative synthesis. The results showed heterogenous protocols with widely different outcomes in depressive symptomatology across the studies, precluding meta-analysis. TMS was considered a safe treatment option with minor side effects. Conclusions: The impact of TMS on depressive symptomatology among chronic pain patients is a complex subject. Considering the diversity of the protocols and results encountered, future research should prioritize the establishment of standardized TMS protocols to clarify its efficacy in managing depressive symptoms among chronic pain patients. Significance: This systematic review highlights the need for further investigation of TMS as a dual therapeutic approach for chronic pain and depressive symptomatology, emphasizing the necessity of improving the protocols to enhance the clinical outcomes.